Media visit to Nyando Climate-Smart Villages - June 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Visit to the Nyando Climate Smart Villages with journalists from the British Broadcasting Corporation and the Kenya Broadcasting Corporation to document ongoing climate change adaptation and mitigation work. Photos: V. Atakos (CCAFS)